2003
DOI: 10.1002/ana.10529
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent changes in the ability to encode a novel elementary motor memory

Abstract: In healthy individuals, motor training elicits cortical plasticity that encodes the kinematic details of the practiced movements and is thought to underlie recovery of function after stroke. The influence of age on this form of plasticity is incompletely understood. We studied 55 healthy subjects and identified a substantial decrease in training-dependent plasticity as a function of age in the absence of differences in training kinematics. These results suggest that the ability of the healthy aging motor corte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(117 citation statements)
references
References 21 publications
7
107
0
3
Order By: Relevance
“…Such concentrations may be reached after chronic administration in patients with Parkinson's disease, who are much older than our subjects (Kornhuber et al, 1995;Verhagen Metman et al, 1998). Although our study sample size does not permit to draw firm conclusions about the role of gender in this type of motor learning, women appeared to perform significantly worser than men in our motor-adaptation task, in accordance with the findings of Sawaki et al (2003), who reported gender differences on a simple motor-learning paradigm using flexion-extension thumb movements. Also, it lends support to the hypothesis that female hormones may modulate neural plasticity and motor-skill learning (Maki et al, 2002;Smith et al, 1999).…”
Section: Discussionsupporting
confidence: 87%
“…Such concentrations may be reached after chronic administration in patients with Parkinson's disease, who are much older than our subjects (Kornhuber et al, 1995;Verhagen Metman et al, 1998). Although our study sample size does not permit to draw firm conclusions about the role of gender in this type of motor learning, women appeared to perform significantly worser than men in our motor-adaptation task, in accordance with the findings of Sawaki et al (2003), who reported gender differences on a simple motor-learning paradigm using flexion-extension thumb movements. Also, it lends support to the hypothesis that female hormones may modulate neural plasticity and motor-skill learning (Maki et al, 2002;Smith et al, 1999).…”
Section: Discussionsupporting
confidence: 87%
“…A forma mais fidedigna de se avaliar a aquisição e desenvolvimento das habilidades necessárias para que o cirurgião possa ser considerado proficiente em videocirurgia, ainda é controversa e, até o momento não há um consenso na literatura sobre os assunto 31,32 . Vários trabalhos foram publicados propondo várias formas de avaliação da proficiência do cirurgião, mas, muitos deles confundiam competência com proficiência.…”
Section: Resultados Resultados Resultados Resultados Resultadosunclassified
“…As médias do número de CVL por ano e as médias do tempo de experiência em videocirurgia e suas associações com lesões da VBP não tiveram diferenças significativas; p=0,31856 e p=0,30722 respectivamente. Da mesma forma, a idade do cirurgião isoladamente não é um fator confiável para previsão de complicações [33][34][35] . A análise estatística mostrou que nesta série houve uma baixa associação entre a idade do cirurgião e as lesões da VBP (coeficiente Phi=0,027603 e coeficiente P de Pearson=0,027592).…”
Section: Resultados Resultados Resultados Resultados Resultadosunclassified
See 1 more Smart Citation
“…For instance, advanced age is linked with reduced capacity for plasticity and is very common in the population of ischemic stroke patients [51,[113][114][115][116][117]. Therefore, it will be necessary to define whether advanced age affects the efficacy of VNS in the context of stroke, in order to determine the patient population most likely to respond to the therapy.…”
Section: Challenges For Translating Vns Therapies Into Clinical Practmentioning
confidence: 99%